Projecting direct medical costs and productivity benefits of improving access to advanced therapy for rheumatoid arthritis: a projection modelling study. Issue 1 (31st December 2023) - Foo, Chee Yoong; Mansor, Nurul Azwani Nadia; Ch'ng, Shereen Suyin; Mohd Zain, Mollyza
ABSTRACT: Introduction: To ensure the sustainability of the AT access improvement, it is important that health system stakeholders have timely, analyzed information accessible for reference and decision-making support. In this study, we projected the direct costs required as well as the expected direct medical cost-offset and productivity benefits resulting from improving the disease control. Methods: We implemented a deterministic, prevalence-based mathematical model to project the annual cost of rheumatoid arthritis (RA) management within the public healthcare system in Malaysia. We also calculated the annual productivity loss due to uncontrolled RA in monetary value. Using the projection model, we compared the projected costs of the status quo scenario vs. several scenarios of improved advanced therapy (AT) access over a 5-year period. Results: We projected that between 10, 765 and 11, 024 RA patients in Malaysia over the period of 2020–2024 will need access to AT due to treatment failure with conventional synthetic disease modifying antirheumatic drugs (DMARDs). The projected net total medical cost under the status quo scenario were 163.5 million annually on average (approximately MYR 15, 000 per patient per year). Cost related to health service utilization represented the heaviest component, amounting to 71.8% followed by drug cost (24.7%). Under the access improvement scenarios, drug cost constituted a higher proportion of the total medical, ranging from 25.6% to 30.4%. In contrast, the cost of health service utilization shown a reverse pattern (reducing to between 66.3% and 70.1%). Productivity costs were also expected to reduce as AT access improved leading to better outcomes. Treatment shifts to targeted synthetic DMARDs in anticipation of price adjustment appeared to have a cost saving advantage to the health system if all other parameters remain unchanged. Discussion: Improving AT access for RA patients towards the aspirational target appeared to be feasible given the current health budget in Malaysia. Broader socio-economic consequences of productivity and income loss should be included as an important part of the policy consideration. The financial implication of different AT utilization mixes and the anticipated price adjustment will likely result in some cost saving to the health system.